Use of CT to evaluate and compare intranasal features in brachycephalic and normocephalic dogs. (10th August 2016) - Auger, M.; Alexander, K.; Beauchamp, G.; Dunn, M.
Abstract : Objectives: To evaluate and compare nasal mucosal contact, septal deviation and caudal aberrant nasal turbinates in brachycephalic and normocephalic dogs using computed tomography. Methods: Dogs without nasal disease and having undergone computed tomography scan of the head (plica alaris to the cribiform plate) were retrospectively selected and divided into brachycephalic and normocephalic groups. Eighteen brachycephalic and 32 normocephalic dogs were included. Anatomic criteria were used to locate predetermined pairs of intranasal structures and nasal mucosal contact was described as present or absent for each site. Septal deviations were identified and measured using angle of septal deviation. Caudal aberrant nasal turbinates were identified and categorised when present. Results: Prevalence of nasal mucosal contact was significantly higher in brachycephalic dogs. No significant difference was seen in prevalence or in angle of septal deviation between groups. Prevalence of caudal aberrant nasal turbinates was significantly higher in brachycephalic dogs. Clinical Significance: Nasal mucosal contact and caudal aberrant nasal turbinates were significantly more prevalent in brachycephalic dogs than in normocephalic dogs in our study. Computed tomography can be a valuable aid in obtaining data on nasal mucosal contact, caudal aberrant nasal turbinates and septal deviations. Combination of computed tomography with endoscopy and functional airway testing would be useful to further evaluate the correlation between intranasal features and symptoms of brachycephalic airway syndrome.